Conflicts management, social capital and adoption of agroforestry technologies : Empirical findings from the highlands of southwestern Uganda - Sanginga, Pascal C.; Kamugisha, R.N.; Martin, A.M. (Springer, 2007)
In the highland ecosystems where actions by some individuals or groups often generate off-site effects among a wide range of social actors and stakeholders, the use and management of natural resources are susceptible to multiple forms of conflicts. This paper examines the hypothesis that conflicts constrain the adoption of agroforestry technologies. Using empirical data from 243 households in Kabale-Uganda, the study identified over 780 different cases of conflicts, and found positive relationships between certain types of conflicts and adoption of agroforestry technologies. The results of this paper challenge the conventional wisdom that conflicts are pervasive, and that the prevalence of conflicts is a major barrier to the adoption of NRM technologies. On the contrary, they seem to suggest that conflicts may have some positive outcomes; they provide incentives for the adoption of NRM technologies, and can be a potential force for positive social change. Conflicts are an essential feature of NRM in the highland systems and cannot therefore be ignored. What matters is the ways such conflicts are managed and resolved, and transformed into a force for positive change. We found that three dimensions of social capital (collective action, byelaws implementation and linking with local government structures) have increased the ability of communities to manage and transform conflicts into opportunities for collective action. These findings suggest new areas for further investigation to improve understanding of adoption decisions and building local capacity for scaling up the impacts of agroforestry innovations.